Construction quality: the challenges and keys to improvement: A multi-level, exexplorative stydy of the quality management practices in a large swedish construction company - Bartek, Sebastian; Olsson, Elin (My University, 2021)
Lacking construction quality and recurring defects leads to significant costs and inconveniences for companies and customers within the Swedish construction industry. While other industries have implemented formal quality management practices with positive results, the construction industry has had a harder time to implement these ideas effectively. The complex nature of the industry is claimed to make it difficult to implement routines that are easily adopted in other ones, also shaping the general traits and behaviours of the people working in the industry. The aim of this study was to make a multi-level exploration of the quality work of a case company; to investigate both the formally provided routines as well as the actual work in order to outline their quality related challenges. It was found that fundamental aspects of quality management practices suggested in literature were lacking or even missing, especially routines that ensure continuous improvements and organizational learning. Quality does not seem to be prioritized on strategic levels, leading to lacking organizational structures and operational routines, placing the heavy weight of ensuring sufficient quality performance on the shoulders of individual managers at project level. The quality reached comes to depend on the interests, experience and knowledge of the managing individuals, their prerequisites and their ability to cope with those and coordinate their teams. The ultimate balance between formal quality procedures and efforts to foster sufficient quality cultures is yet to be found, but efforts aimed to improve both the formal routines and enhance the collective motivation are needed, and some suggestions of improvements are therefore developed for the case company, addressing them both.
Keywords: Quality Management; Construction Industry; Organizational Learning; Knowledge Transfer; Construction Culture; Quality; Continuous Improvements; Motivation; Defect; Error